Tempo de compressão da artéria radial pós-cinecoronariografia : influência sobre homostasia e ocorrências de complicações vasculares - Campos, Maria Aparecida de Carvalho [UNIFESP] (2017)
Transradial access is the safest technique to perform arterial percutaneous diagnostic and interventional procedures. Mechanical devices are used for effective and in shortest time patent hemostasis, increasing late radial artery patency. However, custom dressing gauze compression is widely used in developing countries for cost containment with ideal time for hemostasis, effectiveness of patent occlusion and effect on late radial artery occlusion largely unknown. Objective: We aimed to compare two different compression times of the radial artery after elective coronary angiography using customized compressive dressing regarding the achievement of hemostasis and vascular immediate and late complications. Method: In a prospective, randomized and controlled study in patients submitted to transradial elective coronary angiography, which were allocated to two study groups: compressive dressing maintained for 30 minutes (G30) or compressive dressing maintained for 60 minutes (G60). Variables related to patients, procedure, occurrence of hemostasis and complications were assessed. Radial artery patency was evaluated with Doppler vascular ultrasonography at the time of removal of the compression as well as at 30 days of follow-up. Results: The sample was consisted of 152 patients in the G30 and 151 in the G60, homogeneously distributed in those two studied groups, which have been through demographic, procedural, hemostasis and also vascular complications characteristics. Hemostasis was obtained in 76.3% from the G30 patients and in 84.2% from the G60 patients in the first evaluation. The occurrence of type I and II hematoma was identified in 14.5% from G30 and 20.5% of patients from the G60 while the immediate radial artery occlusion was found in 13.2% from G30 patients and in 11.9% % from the G60. In the 30-day evaluation, 18 late occlusions were identified, 7 (5.5%) from the G30 and 11 (8.2%) from the G60.Conclusion: The different times of radial artery compression after coronary angiography have not significantly influenced the occurrence of hemostasis and vascular immediate and late complications.